A graph for “Orlando Furioso”. First notes for an experimental study (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
Based on previous research done by Franco Moretti and Michal Ginsburg, the essay deals with simple concepts of social network analysis as a means to explore the plot of Ludovico Ariosto’s Orlando furioso. In particular, this study focuses on two graphs that show the connections between some of the characters in the poem meant to visually demonstrate their initial separation and final reunification in cantos I-XII and XXXIV-XLVI.
Keywords: Social network analysis; Orlando furioso; graphs; plot